2016
DOI: 10.1016/j.icarus.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Space weathering trends among carbonaceous asteroids

Abstract: We present visible spectroscopic and albedo data of the 2.3 Gyr old Themis family and the <10 Myr old Beagle sub-family. The slope and albedo variations between these two families indicate C-complex asteroids become redder and darker in response to space weathering. Our observations of Themis family members confirm previously observed trends where phyllosilicate absorption features are less common among small diameter objects. Similar trends in the albedos of large (>15 km) and small (≤15 km) Themis members su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…Weathering effects on C-class and other low-albedo class asteroids have been less well understood. At VNIR wavelengths, both spectral bluing and reddening of VNIR asteroid spectra have been attributed to weathering (e.g., Kaluna et al, 2016;Lazzarin et al, 2006;Nesvorny et al, 2005).…”
Section: Links With Space Weatheringmentioning
confidence: 99%
“…Weathering effects on C-class and other low-albedo class asteroids have been less well understood. At VNIR wavelengths, both spectral bluing and reddening of VNIR asteroid spectra have been attributed to weathering (e.g., Kaluna et al, 2016;Lazzarin et al, 2006;Nesvorny et al, 2005).…”
Section: Links With Space Weatheringmentioning
confidence: 99%
“…Observations of the C-complex, Themis asteroid family and its younger sub-family, the Beagle asteroids, show spectral reddening with increasing age (Kaluna et al 2016b;Fornasier et al 2016). Due to their common origin (Hirayama 1918;Nesvorný et al 2008) and similarity in spectral features (Kaluna 2015;Kaluna et al 2016a), the observed spectral reddening among these two families is unlikely the result of compositional heterogeneity (Kaluna et al 2016b). Though the Themis and Beagle asteroid families provide a useful tool to study space weathering, they are currently the only known C-complex asteroids that originate from the same parent body while having different dynamical (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, both reddening and bluing trends have been observed among C-complex asteroids. However, Lazzarin et al (2006) and Kaluna et al (2016b) suggest the bluing trend found by Nesvorný et al (2005) arises from compositional variations rather than space weathering processes. Observations of the C-complex, Themis asteroid family and its younger sub-family, the Beagle asteroids, show spectral reddening with increasing age (Kaluna et al 2016b;Fornasier et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the simultaneous detection of some objects with phyllosilicate absorption features and the presence of the apparently ice-bearing 133P in the family, Kaluna et al (2016) concluded that the Beagle parent body was most likely composed of a heterogeneous mixture of ice and aqueously altered material. Meanwhile, spectroscopic observations of samples of both Beagle and Themis family asteroids showed that Beagle family asteroids are spectrally bluer, have higher albedos, and exhibit smaller spectral slope variability than background Themis family asteroids, suggesting that the Beagle parent body could have been a particularly blue and bright interior fragment of the original Themis parent body (Fornasier et al 2016).…”
Section: The Themis and Beagle Familiesmentioning
confidence: 99%